2013
DOI: 10.1002/crat.201200512
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of macrostep formation in solution growth of compound semiconductor and the evidence given by space experiment

Abstract: The behavior of macrostep and its formation mechanism are discussed taking solution growth of compound semiconductor as an example. The macrosteps are created by the bunching of atomic steps on a misoriented substrate and they coalesce to form larger macrosteps. At a steady state, the vertical growth of the macrostep terrace is carried out by the atomic steps supplied from a screw dislocation. Space experiments conducted by the group of Professor K. W. Benz showed that the macrostep disappears under a temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This is because the large diffusion coefficient promotes the transport of the solute to the growth interface. Besides, it has previously been observed that the macrostep height is associated with step stability. , Higher steps tend to meander, and the protruding segments in the meander capture more adatoms and grow faster, elevating the step instability . In addition, it was shown in our previous experimental study that by adjusting the flow velocity and direction of the solution, the macrostep height and stability can be controlled, and the inclusions in SiC crystals are expected to be suppressed as well. , Therefore, the effect of the C diffusion coefficient, macrostep height, and solution flow on cellular structure formation should also be considered in SiC solution growth.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is because the large diffusion coefficient promotes the transport of the solute to the growth interface. Besides, it has previously been observed that the macrostep height is associated with step stability. , Higher steps tend to meander, and the protruding segments in the meander capture more adatoms and grow faster, elevating the step instability . In addition, it was shown in our previous experimental study that by adjusting the flow velocity and direction of the solution, the macrostep height and stability can be controlled, and the inclusions in SiC crystals are expected to be suppressed as well. , Therefore, the effect of the C diffusion coefficient, macrostep height, and solution flow on cellular structure formation should also be considered in SiC solution growth.…”
Section: Introductionmentioning
confidence: 86%
“…Besides, it has previously been observed that the macrostep height is associated with step stability. 18,19 Higher steps tend to meander, and the protruding segments in the meander capture more adatoms and grow faster, elevating the step instability. 20 In addition, it was shown in our previous experimental study that by adjusting the flow velocity and direction of the solution, the macrostep height and stability can be controlled, and the inclusions in SiC crystals are expected to be suppressed as well.…”
Section: Introductionmentioning
confidence: 99%
“…16,17) This has been confirmed by micro-gravity experiments conducted in a space shuttle. [18][19][20] It was also found that the impurity nonuniformity is induced in association with macrostep risers. 21) Figure 10 shows a surface micrograph of LPE-grown GaP (a) and a photoluminescence image of the cleaved cross section (b).…”
Section: Siliconmentioning
confidence: 96%
“…The great advantage of MBE is the possibility of real-time monitoring of the growth process. Among the many in situ monitoring systems, the RHEED system is most powerful 20) and has become an indispensable tool. In 1981, Harris et al found that during the growth of GaAs by MBE, the intensity of the RHEED image oscillates with an oscillation period identical to the time for GaAs monolayer growth.…”
Section: Molecular Beam Epitaxy and Metalorganic Chemical Vapor Deposmentioning
confidence: 99%
“…The microgravity conditions suppress convection in a melt, offering quiescent, diffusion-limited growth that eliminates unexpected striations in the grown crystals , and homogeneous doping by unidirectional solidification in the regime of 1 < k (where k ≡ C S / C L is the segregation coefficient and C S and C L denote the solid and liquid concentrations, respectively) . Recently, microgravity experiments for a dilute solution demonstrated long-range, long-duration concentration fluctuations in the solutions caused by thermophoretic flux .…”
Section: Introductionmentioning
confidence: 99%